Pemanfaatan Aplikasi Statistical Package for the Social Sciences (SPSS) dalam Mengelola Data Hasil Penelitian Bagi Calon Guru Fisika - Kaso Sanusi, Dirgah; Agustini, Sri; Rezki Hamzah, Ria; Riskawati, Riskawati; Arief Fitrah Istiyanto Aslim, Muhammad (Education and Talent Development Center Indonesia, 2025)
This community service program aims to enhance the data analysis skills of prospective physics teachers through training in the use of the Statistical Package for the Social Sciences (SPSS). The training was conducted online over three sessions from May 16–18, 2025, involving students currently completing their final projects in the Physics Education Program at Universitas Negeri Makassar. The program included conceptual review of basic statistics, direct SPSS practice, and independent evaluation. Participants were introduced to descriptive, inferential, associative, comparative, and multivariate statistical analysis using SPSS. The results show a positive response and high enthusiasm among participants, particularly during hands-on practice sessions. Evaluation outcomes indicated that most students were able to manage and analyze research data accurately and effectively. This activity not only improved students' technical competencies but also supported their academic readiness and professional development as future educators in the field of physics.